Sex specificity of pancreatic cancer cachexia phenotypes, mechanisms, and treatment in mice and humans: role of Activin. Issue 4 (5th May 2022) - Zhong, Xiaoling; Narasimhan, Ashok; Silverman, Libbie M.; Young, Andrew R.; Shahda, Safi; Liu, Sheng; Wan, Jun; Liu, Yunlong; Koniaris, Leonidas G.; Zimmers, Teresa A.
Abstract: Background: Cachexia is frequent, deadly, and untreatable for patients with pancreatic ductal adenocarcinoma (PDAC). The reproductive hormone and cytokine Activin is a mediator of PDAC cachexia, and Activin receptor targeting was clinically tested for cancer cachexia therapy. However, sex‐specific manifestations and mechanisms are poorly understood, constraining development of effective treatments. Methods: Cachexia phenotypes, muscle gene/protein expression, and effects of the Activin blocker ACVR2B/Fc were assessed in LSL‐Kras G12D/+, LSL‐Trp53 R172H/+, and Pdx‐1‐Cre (KPC) mice with autochthonic PDAC. Effects of PDAC and sex hormones were modelled by treating C2C12 myotubes with KPC‐cell conditioned medium (CM) and estradiol. Muscle gene expression by RNAseq and change in muscle from serial CT scans were measured in patients with PDAC. Results: Despite equivalent tumour latency (median 17 weeks) and mortality (24.5 weeks), male KPC mice showed earlier and more severe cachexia than females. In early PDAC, male gastrocnemius, quadriceps, and tibialis anterior muscles were reduced (−21.7%, −18.9%, and −20.8%, respectively, all P < 0.001), with only gastrocnemius reduced in females (−16%, P < 0.01). Sex differences disappeared in late PDAC. Plasma Activin A was similarly elevated between sexes throughout, while oestrogen and testosterone levels suggested a virilizing effect of PDAC in females. Estradiol partially protected myotubes from KPC‐CM induced atrophy and promoted expression of the potential Activin inhibitor Fstl1. Early‐stage female mice showed greater muscle expression of Activin inhibitors Fst, Fstl1, and Fstl3; this sex difference disappeared by late‐stage PDAC. ACVR2B/Fc initiated in early PDAC preserved muscle and fat only in male KPC mice, with increases of 41.2%, 52.6%, 39.3%, and 348.8%, respectively, in gastrocnemius, quadriceps, tibialis, and fat pad weights vs. vehicle controls, without effect on tumour. No protection was observed in females. At protein and RNA levels, pro‐atrophy pathways were induced more strongly in early‐stage males, with sex differences less evident in late‐stage disease. As with mass, ACVR2B/Fc blunted atrophy‐associated pathways only in males. In patients with resectable PDAC, muscle expression of Activin inhibitors FSTL1, FSLT3, and WFIKKN2/GASP2 were higher in women than men. Overall, among 124 patients on first‐line gemcitabine/nab‐paclitaxel for PDAC, only men displayed muscle loss ( P < 0.001); average muscle wasting in men was greater (−6.63 ± 10.70% vs. −1.62 ± 12.00% mean ± SD, P = 0.038) and more rapid (−0.0098 ± 0.0742%/day vs. −0.0466 ± 0.1066%/day, P = 0.017) than in women. Conclusions: Pancreatic ductal adenocarcinoma cachexia displays sex‐specific phenotypes in mice and humans, with Activin a preferential driver of muscle wasting in males. Sex is a major modulator of cachexia mechanisms. Consideration of sexual dimorphism is essential for discovery and development of effective treatments.